The Global Trade Slowdown : Cyclical or Structural? - Constantinescu, Cristina (IMF Working Papers; Working Paper ;, 2015)
This paper focuses on the sluggish growth of world trade relative to income growth in recent years. The analysis uses an empirical strategy based on an error correction model to assess whether the global trade slowdown is structural or cyclical. An estimate of the relationship between trade and income in the past four decades reveals that the long-term trade elasticity rose sharply in the 1990s, but declined significantly in the 2000s even before the global financial crisis. These results suggest that trade is growing slowly not only because of slow growth of Gross Domestic Product (GDP), but also because of a structural change in the trade-GDP relationship in recent years. The available evidence suggests that the explanation may lie in the slowing pace of international vertical specialization rather than increasing protection or the changing composition of trade and GDP.